1998
DOI: 10.1080/002202798183530
|View full text |Cite
|
Sign up to set email alerts
|

Close encounters: Truth, experience and interpretation in multicultural teacher education

Abstract: his paper examines the contradictory e ects of teaching multicultural education in two American white women' s university classrooms. T he authors use discourse analysis to understand the confusing results of teaching about di erence. In this analysis, course readings and a ® eld trip to an urban school are examined in regard to the instructors' intentions and students' responses. T he authors understand the puzzling results of their teaching by examining the positivist dimensions of their pedagogy, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 13 publications
(19 reference statements)
0
27
0
Order By: Relevance
“…A related difficulty is that white teachers themselves can be equally socially and emotionally invested in these discourses, and do not always receive multicultural or anti-racist education in the way that teacher educators intend (Lesko and Bloom 1998). In other words, learners--whether children or adults--can be deeply resistant to the kinds of knowledge which demand that they engage with difficult truths about themselves and their world that can be very difficult to tolerate or to accept.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A related difficulty is that white teachers themselves can be equally socially and emotionally invested in these discourses, and do not always receive multicultural or anti-racist education in the way that teacher educators intend (Lesko and Bloom 1998). In other words, learners--whether children or adults--can be deeply resistant to the kinds of knowledge which demand that they engage with difficult truths about themselves and their world that can be very difficult to tolerate or to accept.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, learners--whether children or adults--can be deeply resistant to the kinds of knowledge which demand that they engage with difficult truths about themselves and their world that can be very difficult to tolerate or to accept. Drawing on their experiences of attempting to engage predominantly white, middleclass teacher education students with the 'truth' about social injustices and inequalities, Lesko and Bloom (1998) show how knowledge is constrained by epistemological and discursive limits. It would be naïve to suggest, therefore, that the act of replacing 'bad ideas' about race and racism in the curriculum with 'good' ones, will, in and of itself, radically disrupt the existing racial status quo.…”
Section: Discussionmentioning
confidence: 99%
“…When resisters discussed educating students in an urban environment, they focused on beliefs that students are not self-disciplined and lack respect for teachers; emphasizing their desire to teach in their monocultural comfort zone (Lesko and Bloom 1998). Rushton (2003) suggested that preservice teachers have preconceived ideas about urban environments, but come to grow and change their beliefs after new experiences.…”
Section: Closing Thoughtsmentioning
confidence: 99%
“…However, the effectiveness of these classes has been questioned (Garmon 2004;Larke 1990; Lesko and Bloom 1998;Wideen, Mayer-Smith, and Moon 1998) because most colleges of education are flouting this evolving mandate by offering only one course that is at best dismissive and pacifist, and at worst ineffective in meeting the needs of diverse learners.…”
mentioning
confidence: 97%
“…length depending on the period of time for which a respondent spoke, which might be very brief or more prolonged. The analysis paid close attention to how leaders construct meanings; of 'difference' and equality, and how they formulated action in response (Lesko & Bloom, 1998). Consequently the data was coded using themes related to concepts of diversity, the perceived pressures to consider diversity, the relevance of diversity, actions to achieve diversity and personal experience of diversity issues.…”
Section: Case Methodsmentioning
confidence: 99%